Lead Prioritization: A guide to maximizing sales using analytics and AI in Real Estate - Goel, Krupa (Eastasouth Institute, 2024)
In this highly competitive market, selecting the right lead that would bring significant sales conversion is one of the keys to an effective real estate business. In the following paper, we discuss the function of analytics and artificial intelligence in transforming lead management in the real estate industry. Conventional methods of lead prioritizing involve the rote use of the gut feeling of a salesperson, which, although inefficient, leaves much room for potential errors. Incorporating AI and analytics lead management thrust real estate agents into data analysis, where agents can make predictive and behavioral decisions based on stated data. Through lead scoring tools and other intelligent platforms such as AI, an agent can determine high probable lead conversion, directing efforts to more converting leads. Furthermore, this paper examines the use of big data analytics in predicting market trends and buying behavior to improve the position of agents competing in a highly technological marketplace. The paper also discusses changes in buyers' needs, including the interest in customization and environmental sustainability, which are gaining importance in lead selection processes. For this, adopting these technologies not only makes operations more efficient but also assists agents in building better client relations by initiating marketing that would capture the clients' interest and subsequently follow up on them. The lead management of the real estate industry will only improve due to enhanced artificial intelligence and analytics in the future. This paper acts as a reference for real estate agents trying to incorporate current tools in managing their leads to improve their chances of closing deals.